Tracking HIV-1 recombination to resolve its contribution to HIV-1 evolution in natural infection - Hongshuo Song (Nature Portfolio, 2018)
Recombination contributes to HIV evolution in patients, but its identification can be difficult. Here, the authors develop a computational tool called RAPR to track recombination in patients, identify recombination hot spots, and show contribution of recombination to antibody escape.